Des données de terrain à la conception d'outils de médiation de l'information : Élaborer une démarche d'information adaptée à destination des MNA - Isabelle Estève (Université de Provence, 2019)
We will present the design process of the visual welcome booklet and its user guide that we conceived in the MIMNA project (Mediation of Information for Unaccompanied Minors). Crossing the expertise of professionals working with unaccompanied minors and a sociolinguistic approach to mediation issues led us formalise mediation principles and strategies, based on field data. These mediations tools have been developed as part of an information approach effectively adapted to Unacompanied Minors. We understand by adapted information: it allows the Unacompagnied Minors not only to activate meaning but also to appropriate the information and to build knowledge that is meaningful to him/her.